Algal-algal bioflocculation enhances the recovery efficiency of Picochlorum sp. QUCCCM130 with low auto-settling capacity - Imen Saadaoui (14159025) (2023)
Large-scale production of microalgal biomass is still considered non-viable due to the high cost and energy required for harvesting. A fast, cost-effective, and successful harvesting technique has become widely sought after in microalgal biotechnology applications. Algal-algal bioflocculation was adopted for the current study, pH and the ratio between species were selected as two parameters to be optimised. Picochlorum sp. QUCCCM130, Nannochloris sp. QUCCCM31 and Tetraselmis sp. QUCCCM50 presenting a cell size of ∼2 μm, ∼5 μm, and ∼15 μm, respectively, were selected to be subjected to the harvesting optimisation experiments. Results showed that self-settlement capacity increased with cell size and can be indirectly related to a decreased zeta potential of larger cells which enhances the Van der Waals attractive forces. Furthermore, it was noted that pH enhanced the self-settlement capacity of small-sized cells as well that are unable to self-settle. Algal-algal bioflocculation efficiency is dependent on the ratio between species with different sizes, increasing with a higher proportion of larger size microalgal cells. Mixing three microalgae together at pH 10 led to the appearance of large flocs in which the larger cells surrounded the smaller cells. Microscopic observation confirmed that Tetraselmis sp. held the small cells inside the flocs using their flagella. Thus, we can conclude that mixing microalgal cells in a specific ratio and at a specific pH increases the recovery efficiency of small-sized microalgae that can be difficult to harvest, such as Picochlorum sp. QUCCCM130. Other Information Published in: Algal Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.algal.2023.103038